Omni-channel shopping experiences – to share or not to share? - Melanie Wiese (Cogent Business & Management, 2024)
This study proposes an extended Stimulus-Organism-Response framework that investigates perceived seamlessness and product information as drivers of omni-channel shopping satisfaction, as well as the resulting consumer response outcomes. There is a specific focus on consumption and experience-sharing behaviour and on the moderating role of social media attractiveness. An online self-administered questionnaire resulted in 433 responses from South African shoppers. The hypotheses were tested using structural equation modelling and a multi-group CFA approach. Interestingly, information visibility was the strongest predictor of satisfaction. Furthermore, convenience of sharing was confirmed as a mediator, while social media attractiveness acted as moderator in the relationship between satisfaction and experience sharing. The research contributes to the fast-growing trend of omni-channel retailing, especially from a consumer perspective. While research typically focuses on consumption-sharing behaviour, this study adopted a dual-sharing perspective by investigating not only customer influence as a type of consumption behaviour sharing, but also experience sharing behaviour. The applicability of an extended S-O-R framework is confirmed in an emerging market context while providing practical insights for retailers.
Keywords: 650; seamlessness; omni-channel; satisfaction; customer influence; experience sharing; social media attractiveness